2017
DOI: 10.1080/14756366.2017.1347167
|View full text |Cite
|
Sign up to set email alerts
|

Water permeability is a measure of severity in acute appendicitis

Abstract: Acute appendicitis is the most common indication for pediatric abdominal emergency surgery. Determination of the severity of appendicitis on clinical grounds is challenging. Complicated appendicitis presenting with perforation, abscess or diffuse peritonitis is not uncommon. The question remains why and when acute appendicitis progresses to perforation. The aim of this study was to assess the impact of water permeability on the severity of appendicitis. We show that AQP1 expression and water permeability in ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Similar results were obtained by Pini et al (2017), who studied the influence of appendicitis on the distribution of AQP1 in the wall of the appendix. In that study, AQP1 was observed in the enteric ganglia in cells, which were not immunoreactive to panneronal marker -microtubule associated protein 2 (MAP-2), which suggests that (as in the oesophagus) AQP1 is present in glial cells, not in neurons.…”
Section: Humanssupporting
confidence: 85%
See 4 more Smart Citations
“…Similar results were obtained by Pini et al (2017), who studied the influence of appendicitis on the distribution of AQP1 in the wall of the appendix. In that study, AQP1 was observed in the enteric ganglia in cells, which were not immunoreactive to panneronal marker -microtubule associated protein 2 (MAP-2), which suggests that (as in the oesophagus) AQP1 is present in glial cells, not in neurons.…”
Section: Humanssupporting
confidence: 85%
“…In that study, AQP1 was observed in the enteric ganglia in cells, which were not immunoreactive to panneronal marker -microtubule associated protein 2 (MAP-2), which suggests that (as in the oesophagus) AQP1 is present in glial cells, not in neurons. A higher number of AQP1-positive cells were noted in the myenteric ganglia than the submucous ganglia (Pini et al, 2017). In the same study, AQP1positive nerve fibres were observed in the neuronal ganglia in the wall of the appendix (Pini et al, 2017).…”
Section: Humanssupporting
confidence: 52%
See 3 more Smart Citations